Clay and Shale Slope Instability 1995
DOI: 10.1130/reg10-p139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of argillic alteration on rock mass stability

Abstract: The role of hydrothermal alteration in producing clay-rich rocks is discussed. Hydrothermal fluids derived from magmatic sources change rock lithologies to argillic rocks as a result of temperature, pressure and chemical effects. The grade of the argillization can vary from one in which only trace amounts of clay minerals are present to one in which there has been complete alteration into clay. Detailed geologic surface mapping and subsurface drilling are required to accurately delineate the extent and grade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Other tests on remolded volcanic granular flow materials showed decreases in frictional strength of 3-11% (Samuelson et al 2008). For comparison, extensive acid sulfate-argillic alteration of volcanic rocks, without undergoing large strain, can reduce frictional strength by 30-65% (Watters and Delahaut 1995;Zimbelman et al 2004).…”
Section: Shear Strength Of Dome Rocksmentioning
confidence: 92%
“…Other tests on remolded volcanic granular flow materials showed decreases in frictional strength of 3-11% (Samuelson et al 2008). For comparison, extensive acid sulfate-argillic alteration of volcanic rocks, without undergoing large strain, can reduce frictional strength by 30-65% (Watters and Delahaut 1995;Zimbelman et al 2004).…”
Section: Shear Strength Of Dome Rocksmentioning
confidence: 92%
“…The second part included the collection of representative samples from which intact rock strengths, joint and infilling material strengths, and the type and intensity of alteration were evaluated. For the geotechnical component, hydrothermal alteration classification was based on visual observations, as described in Watters and Delhaut (1995), which varies from an intensity of zero (no alteration) to four (complete replacement of phenocrysts and matrix). …”
Section: Geotechnical Studiesmentioning
confidence: 99%
“…Of these factors, seismic forces and fluid pressures are generally studied after slope failure or volcanic activity, whereas rock strengths and stabilities can be calculated and evaluated prior to an event. For example, Reid et al (2000), using data from Voight et al (1983) and Watters and Delhaut (1995), concluded that the depth and volume of a failure mass is dependent on the rock strength. A key component in edifice stability, therefore, is the assessment of rock mass strength and its spatial distribution, including within the volcanoes interior.…”
Section: Introductionmentioning
confidence: 99%
“…The diamine putrescine is synthesized from arginine and ornithine via the rate-limiting enzymes arginine decarboxylase (ADC) and ornithine decarboxylase (ODC), respectively. Higher plants and bacteria use both the ADC and ODC pathways for synthesising polyamines, while fungi possess only ODC for polyamine biosynthesis [3,4]. It should be possible, therefore, to control fungal polyamine biosynthesis by specifically inhibiting ODC without affecting plant growth and development [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%